Psychometric evaluation of the Persian version of the Successful Aging Inventory: - Sharifi, Khadijeh; Fazeli Tarmazdi, Masoumeh; Tagharrobi, Zahra; Sooki, Zahra (Galen Medical Journal, 2020)
Background: The first step to successful aging planning is to assess the current status using valid instruments. This study aimed to evaluate the psychometric properties of the Persian version of the Successful Aging Inventory (SAI). Materials and Methods: In the first step, SAI. was translated through forward-backward translation, and its face and content validity were qualitatively and quantitatively assessed. For construct validity assessment, 300 elderly were recruited through multi-stage random sampling. Exploratory factor analysis and known-group comparison were used. SAI reliability through internal consistency and stability was assessed using the Cronbach’s alpha values of the inventory and intraclass correlation coefficient (ICC), respectively. The standard error of measurement, smallest detectable change, and floor and ceiling effects were calculated. Results: The impact scores, content validity ratios, and content validity indices of all items were more than 1.5, 0.62, and 0.8, respectively. The scale-level content validity index was 0.94. Factor analysis identified four factors for the inventory, which explained 58.17% of the total variance of the SAI score. SAI mean score among mentally healthy participants was significantly higher (P<0.001). The relative frequencies with the lowest and highest possible scores of SAI were 0 and 3.7%, respectively. The Cronbach’s alpha, ICC, standard error of measurement, and the smallest detectable change of SAI were 0.835, 0.999, ±0.47, and 1.9, respectively. Conclusion: As a valid and reliable instrument, the Persian version of SAI could be used for a successful aging assessment. [GMJ.2020;9:e1754]